STUDY OF THE QUALITY (PHYSIOCHEMICAL PARAMETER) OF HONEY CARRIED OUT IN THE ANNABA REGION (NORTH-EASTERN ALGERIA) - BOUSSATHA, ANISSA; FATIHA, BOUOUZA; ADJABI, NESRINE (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The most widely used honey bees for beekeeping are European races of Apis mellifera, species of honey bees that also originate from Africa and the Middle East. Honey is a product largely known and used in our country. However, in Algeria honey is consumed in great quantity. This natural product is not sowing with a quality control and the consumer is exposed at the risks of health. In the Européenne and American scale there is an international commission of quality control and which definite standards of quality of honey. In this context we proposed to analyze some varieties of honey collected in the Algerian East in the bee-keeping occupies a place of choice in agriculture and two imported varieties. In addition Algeria imports each year of the considerable quantities of honey. This research task thus made it possible to study certain properties Physicochemical (pH, moisture, conductivity, HMF, an acidity). These allow us to identify the different properties of the honeys harvested in the Annaba region.